Nisekoi, false love. Vol. 16, Look-alike - Komi, Naoshi, 1986- (Viz Media, 2016)
"English teacher Yui has been assigned to take over as the school music teacher?! She's so tone-deaf her singing makes the students faint, and yet she's been chosen to sing in front of the whole school! Later, Raku and Chitoge are in for a surprise when they meet a princess from a foreign kingdom--who looks exactly like Chitoge! What's in store when the princess and Chitoge switch places?"--Amazon.com